Constructing a multidimensional indicator for Islamic finance development - Idah Zuhroh; Nazaruddin Malik; Muhammad Khoirul Fuddin; Fitri Rusdianasari (Journal of Innovation in Business and Economics, 2025)
This study conducts a systematic literature review to evaluate existing indicators used in measuring Islamic finance development and proposes the Islamic Finance Development Indicator Plus (IFDI+), a multidimensional framework that extends beyond asset-based and compliance-oriented metrics. A total of 51 peer-reviewed articles published between 2019 and 2025 were analyzed following PRISMA standards, complemented by bibliometric mapping using VOSviewer. The review identifies five core dimensions essential for assessing Islamic finance development: 1) quantitative development, 2) governance and regulatory quality, 3) innovation and technology adoption, 4) social impact and economic inclusion, and 5) awareness and financial literacy. The IFDI+ framework integrates these dimensions into a cohesive evaluative model aligned with maqasid al-shariah and contemporary sustainability agendas. This study contributes to improving measurement practices and provides guidance for policymakers in strengthening multidimensional reporting, supporting fintech-enabling regulatory environments, and enhancing ESG and financial inclusion initiatives. Future research should operationalize and empirically validate IFDI+ across diverse jurisdictions.